THE EFFECT OF MERGER FLOW CURRENT ON U-TURN ON TRAFFIC FLOW CHARACTERISTICS ON A. YANI ROAD KM. 35 IN BANJARBARU CITY - Kamila, Cahya; Radam, Iphan Fitrian (CERUCUK, 2024)
The denser an area is, the denser the traffic movement will be. When the vehicle makes a u-turn movement, it can cause congestion because the vehicle doing a u-turn causes the vehicle volume to get higher and the vehicle speed lower.   Jalan A. Yani Km. 35 in Banjarbaru city South Kalimantan province is one of the road sections that connect people to and from the city center.  The road has median and median openings to coordinate the u-turn movement.  This study aims to determine the performance of traffic that is affected by u-turn and not affected by u-turn.   The research was conducted using a field survey method that included traffic volume, vehicle speed and geometric road conditions. The method for analyzing data uses conventional methods (Greenshield, Greenberg, and Underwood models), and the best model relationship is obtained, namely the Greenshield model. From the calculation results of the Level of Service, for road conditions affected by the u-turn LOS the dominant E was 68% with a saturation degree value ranging from 0.88 – 1.00, which occurred at 16.00 – 17.30 CIT and 17.30 – 21.00 CIT.  Meanwhile, road conditions that are not affected by the u-turn LOS obtained  C of 72% with a saturation degree value ranging from 0.45 – 0.60.Keywords: Level of Service, Merger, Traffic Flow Characteristics, U-Turn